A semi-Analytical Dispersion Model from a Steady Source of Short Duration - Moreira, Davidson Martins (Ciência e Natura, 2014)
This paper presents a semi-analytical unsteady-state solution to the atmospheric dispersion equation for substances subject to chemical-physical decay and that allows a description of the time evolution of the concentration field emitted from a source during a release of short duration. This solution is suitable for describing critical events relative to accidental release of toxic, flammable or explosive substances. The results of the sensitivity analysis and of validation testing, with a proper parameterization of the vertical profiles of the wind and eddy diffusivities, were evaluated against experimental data found in the literature.